2013
DOI: 10.1175/jtech-d-12-00116.1
|View full text |Cite
|
Sign up to set email alerts
|

Determination of Planetary Boundary Layer Height on Short Spatial and Temporal Scales: A Demonstration of the Covariance Wavelet Transform in Ground-Based Wind Profiler and Lidar Measurements*

Abstract: This article explores the application of the covariance wavelet transform (CWT) to lidar and, for the first time to the authors' knowledge, wind profiler data to examine the possibility of accurate and continuous planetary boundary layer (PBL) height measurements on short temporal resolution (1- and 15-min averages, respectively). Determining the mixing in the PBL was one goal of a study of the spatial and diurnal variations of the PBL height over Maryland for July 2011, during NASA's Earth Venture mission DIS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
66
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 75 publications
(67 citation statements)
references
References 12 publications
1
66
0
Order By: Relevance
“…As with previous studies (Brooks, 2003;Baars et al, 2008;Compton et al, 2013;Scarino et al, 2014), the dilation factor a affects the number of covariance wavelet transform coefficient (CWTC) local minimums. Larger values create a few large local minimums (Fig.…”
Section: Haar Wavelet Methodsmentioning
confidence: 64%
See 3 more Smart Citations
“…As with previous studies (Brooks, 2003;Baars et al, 2008;Compton et al, 2013;Scarino et al, 2014), the dilation factor a affects the number of covariance wavelet transform coefficient (CWTC) local minimums. Larger values create a few large local minimums (Fig.…”
Section: Haar Wavelet Methodsmentioning
confidence: 64%
“…Out of the three methods tested in this study, it is suggested to employ the wavelet method in future studies, in particular for longterm seasonal and diurnal boundary layer studies and spatial analysis of the BL using multiple lidar aerosol backscatter measurements. A combination of the wavelet method BLH retrievals during clear skies and the cluster analysis method's ability to calculate cloud depth is also recommended for more robust BL studies to retrieve more information about the boundary layer under both conditions, as both the wavelet and cluster analysis methods were seen to perform well using various lidar instruments in studies such as Compton et al (2013), Scarino et al (2014), and Toledo et al (2014). Although not tested in this study, recent work by de Bruine et al (2016) and Poltera et al (2017) show promising results using an automated method which reduces incorrect detection of the BLH using graph theory.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…CLN is comprised of lidar facilities at mainly 4 sites (campuses) supported by the NOAA CREST Center (see Fig.1 [5,6,7]. The high pulse powers allow the observation and quantification of multi-layer plumes; and the multiwavelength capacity enables us to classify aloft aerosol type (smoke or dust).…”
Section: Lidar System and Methodologymentioning
confidence: 99%